2017
DOI: 10.14196/mjiri.31.61
|View full text |Cite
|
Sign up to set email alerts
|

The paced auditory serial addition test for working memory assessment: Psychometric properties

Abstract: Background: The paced auditory serial addition test (PASAT) was primarily developed to assess the effects of traumatic brain injury on cognitive functioning. Working memory (WM) is one of the most important aspects of cognitive function, and WM impairment is one of the clinically remarkable signs of aphasia. To develop the Persian version of PASAT, an initial version was used in individuals with aphasia (IWA). Methods: In this study, 25 individuals with aphasia (29-60 years) and 85 controls (18-60 years) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Respondents summed the last number with the new number and verbal responses were recorded. The PASAT was chosen for its reliability ( r = 0.95; Nikravesh et al, 2017) and sensitivity in aging adults (Tombaugh, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Respondents summed the last number with the new number and verbal responses were recorded. The PASAT was chosen for its reliability ( r = 0.95; Nikravesh et al, 2017) and sensitivity in aging adults (Tombaugh, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…CORRELATES OF THE PASAT attention. Accordingly, poor performance on the PASAT may suggest deficits in working memory, or overall executive functioning, but not necessarily ADHD (e.g., Nikravesh et al, 2017). In addition, outperformance on select trials of the PASAT may be indicative of strong processing speed or math ability, but these strengths may not manifest across all trials.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the PASAT is frequently included in ADHD assessments (e.g., Bottini et al, 2019; Nikolas et al, 2019), but the results of this study demonstrated that the PASAT does not correlate strongly with subjective and objective measures of attention. Accordingly, poor performance on the PASAT may suggest deficits in working memory, or overall executive functioning, but not necessarily ADHD (e.g., Nikravesh et al, 2017). In addition, outperformance on select trials of the PASAT may be indicative of strong processing speed or math ability, but these strengths may not manifest across all trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental arithmetic is considered an important cognitive activity and involves several complex processes, including identifying quantities, arranging the quantities into formulas, and then conducting psychological comparisons and calculations [27,28]. The arithmetic test showed good validity and testretest reliability (intra-class correlation = 0.95) [29]. In this study, the mental arithmetic test was delivered in an auditory presentation of random numbers from 0 to 9 with an interval of 2 s between numbers.…”
Section: Mental Stress Testmentioning
confidence: 99%